Antioxidant and Anti-acne Activities of Stingless Bee Honey and Propolis Extract - Wattanuruk, Duangduan; Matintarangson, Nathapong (Journal of Food Health and Bioenvironmental Science, 2024)
Stingless bees form a large group of bees that lack a sting and are found in tropical and sub-tropical areas. Honey and propolis are major products that are produced by the stingless bee. This study aimed to investigate honey and propolis extracts, leading us to isolate bioactive compounds for their antioxidant and anti-acne properties. The four different stingless bee species (Geniotrigona thoracica, Heterotrigona itama, Tetragonula pagdeni, and Lepidotrigona terminate), collected from a community enterprise area (southern Thailand). The raw propolis was extracted via maceration with 20% ethanol. The present study aimed to assess the concentration of phenolics and flavonoids using Folin-Ciocalteu method, Aluminum Chloride Colorimetry method and DPPH respectively, as well as the antibacterial against bacteria Propionibacterium acne (DMST 14917) using the agar well diffusion method. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values were determined by the in vitro method. The findings indicate that G. thoracica honey has the highest content of total phenolic (30.28±0.51 mgGAE/g), flavonoids (59.77±0.05 mgRE/g) and DPPH (1.251±0.27 mg/mL), while the phenolic (25.34±0.06 mgGAE/g), flavonoids (44.33±0.41 mgRE/g) and DPPH (2.210±0.28 mg/mL) of H. itama propolis extract are higher than those of the other extracts.The antibacterial activity of the honey against P. acne was categorized as highly strong inhibitory, while propolis extract was classified as moderate inhibitory. Additionally, G. thoracica honey exhibits the highest antibacterial activity against P. acnes at 37.74±1.5 mm, MIC (62.5 μg/mL) and MBC (125 μg/mL), while H. itama propolis extract was 14.43±2.7 mm, MIC (125 μg/mL) and MBC (250 μg/mL). These results indicated that stingless bee honey and propolis extracts contain valuable quantities of phenolic and flavonoid compounds, which serve as natural anti-oxidants and exhibit notable anti-microbial activity. The results suggest that stingless bee products hold commercial potential as a natural source of bioactive ingredients to be formulated into cosmetic agents.